2013
DOI: 10.9775/kvfd.2012.8458
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Bitter Melon (Momordica charantia) and Gotu Kola (Centella asiatica) Extracts on Healing of Open Wounds in Rabbits

Abstract: SummaryThis study investigated the eff ects of topically applied oily homogenized and powder forms of bitter melon (Momordica charantia) (MC) and ointment formulation of gotu kola (Centella asiatica) (CA) extract and compared the results with untreated control and pure olive oil groups on wound healing in rabbits. A total of 30 New Zealand rabbits were divided into five equal groups (oily homogenized form of MC, powder form of MC, ointment of CA, control, pure olive oil). Full-thickness 5x5 cm skin wounds were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
(18 reference statements)
0
5
0
2
Order By: Relevance
“…After xylazine hydrochloride (Alfazyne® 2%, Alfasan International B.V. Netherlands) (4 mg/kg, IM) premedication, anesthesia was achieved by ketamine hydrochloride (Alfamine® 10%, Alfasan International B.V. Netherlands) (50 mg/kg, IM) (Satar et al, 2013).…”
Section: Anesthesiamentioning
confidence: 99%
“…After xylazine hydrochloride (Alfazyne® 2%, Alfasan International B.V. Netherlands) (4 mg/kg, IM) premedication, anesthesia was achieved by ketamine hydrochloride (Alfamine® 10%, Alfasan International B.V. Netherlands) (50 mg/kg, IM) (Satar et al, 2013).…”
Section: Anesthesiamentioning
confidence: 99%
“…Several studies demonstrated the effect of C. asiatica in wound healing when topically applied (Gohil et al, ; Gul Satar et al, ; Hong et al, ; Sawatdee, Choochuay, Chanthorn, & Srichana, ). Its mechanism of action has been attributed to increase cellular proliferation and collagen synthesis at the wound site (Pazyar et al, ; Sunilkumar, Parameshwaraiah, & Shivakumar, ), increase in angiogenesis (Incandela et al, ; Rosen, Blumenthal, & McCallum, ), and it has an effect on keratinization, which aids in thickening skin in areas of infection (Poizot & Dumez, ).…”
Section: Centella Asiaticamentioning
confidence: 99%
“…Commercial enzymatic debriding agents are available, and some previous studies reported their efficacy mainly in the treatment of burn wounds (Cordts et al, 2016;Rosenberg et al, 2014;Schulz et al, 2017) and to clear bruises and hematomas on boxers (Blonstein, Bromelain (Dutta & Bhattacharyya, 2013;Ali et al, 2015;Praveen et al, 2014;Manosroi et al, 2014;Ataide, de Carvalho, et al, 2017;Ekambaram et al, 2017) (Dutta & Bhattacharyya, 2013;Hu et al, 2011;Singer et al, 2010;Wu et al, 2012) (Blonstein, 1960;Cordts et al, 2016;Koller et al, 2008;Krieger et al, 2012;Rosenberg et al, 2004;Rosenberg et al, 2014;Schulz et al, 2017) Propolis ( Centella asiatica (Hong et al, 2005;Shukla, Rasik, Jain, et al, 1999;Gohil et al, 2010;Incandela et al, 2001;Zhang et al, 2016) (Shukla, Rasik, Jain, et al, 1999;Sawatdee et al, 2016;Gohil et al, 2010;Gul Satar et al, 2013;Sunilkumar et al, 1998;Rosen et al, 1967;Incandela et al, 2001;Poizot & Dumez, 1978;Suguna et al, 1996;Zhang et al, 2016) …”
Section: Bromelainmentioning
confidence: 99%
“…Kudret narı bitkisinden elde edilen ekstraktların, topikal olarak uygulanarak, yara iyileşmesindeki etkinliğinin incelendiği çalışmalarda, bitkinin sahip olduğu geniş spekturumlu antibakteriyel aktivite, antioksidan, antienflamatuar, analjezik ve antiülser özelliklerinden dolayı yara iyileşmesinde oldukça etkili bir rolü olduğu saptanmıştır [41][42][43][44][45].…”
Section: Kudret Narının Yara İyileşmesindeki Rolüunclassified
“…İlişkin Yapılan Çalışmalar Kudret narı bitkisinin yara iyileşmesindeki etkinliğinin incelendiği deney hayvanlarıyla yapılan çalışmalarda, yara kontraksiyon yeteneği, yara kapanma zamanı, epitelizasyon süreci, yaranın gerilme kuvveti ve yara iyileşme hızı bakımından kudret narının etkili olduğunu gösteren birçok çalışma mevcuttur [41][42][43][44][45][46]60].…”
Section: Kudret Narının Yara İyileştirici öZelliğineunclassified